Vpliv suše na drobne korenine dreves in ektomikorizo v gozdnih ekosistemih - Mrak, Tanja (Acta silvae et ligni, 2019)
Drought stress elicits many changes in tree fine roots and ectomycorrhizal fungi. Trees cope with drought through avoidance mechanisms or tolerance. Drought can result in changes in colonization by ectomycorrhizal fungi and in the structure of ectomycorrhizal communities. Survival of tree seedlings is supported through common mycelium networks. In moderate drought, there is greater colonization by ectomycorrhizal fungi compared to severe drought, resulting in several beneficial effects to the tree. Under drought, the frequency of ectomycorrhizal fungus Cenococcum geophilum Fr. often increases. C. geophilum sustains tree fine roots function and therefore roots are able to absorb water as soon as the drought period is over. Under drought, synthesis of recalcitrant organic compounds in roots, e.g. lignine, is increased. Recalcitrant compounds such as melanine are also found in C. geophilum, contributing to the accumulation of recalcitrant soil organic matter.
Keywords: adaptation; drobne korenine; fine roots; global changes; globalne spremembe; mikorizne glive; mycorrhizal fungi; organska snov v tleh; prilagoditve; soil organic matter